Porque **Ecolinguística** - Makkai, Adam (2015)
Originally published as Introduction to Makkai (1993), this article contains many of the ecolinguistic ideas of the author. Basically, it is an attempt at showing that there are other ways of doing linguistics beyond generative grammar, then called ‘generative transformational grammar’. Among these alternatives the following are mentioned, among others: Pike’s tagmemics, Sydney Lamb’s stratificational grammar and Halliday’s systemic-functional grammar. However, the alternative more in sync with the new view of the world brought about by modern science would be ecolinguistics, which is still in statu nascendi but can be a very interesting starting point for the study of language phenomena. However, it is proposed not as a paradigm for language sciences.